Metamorphic PT path and zircon U-Pb dating of Archean eclogite association in Gridino complex, Belomorian province, Russia - Li, Xiaoli; Zhang, Lifei; Wei, Chunjing; Slabunov, Alexander I. (Precambrian Research, 2015)
The eclogites from the Gridino eclogite-bearing melange complex in the Belomorian province, Fennoscandian Shield may represent one of the oldest terrain in the world. The Belomorian province is a superposition of Archean and Palaeoproterozoic collisional orogens, which experienced repeated high-grade metamorphic reworking and intense polyphase tectonic deformation in the early Precambrian. Main purpose of this study is to determine the metamorphic age(s) and evolutionary PT path of eclogite as boudin-like body within the Gridino tectonic melange. Representative rock materials of well-preserved, plagioclase-free eclogite and associated retrogressed eclogitic rock were sampled from Stolbikha Island in the Gridino area for our research. The eclogite sample mainly comprises omphacite, garnet, amphibole, rare quartz, and some accessory minerals (rutile, magnetite), whereas the retrogressed eclogite sample is made of diopside - Na-rich plagioclase symplectites, amphibole, quartz, and accessory minerals. Thermodynamic modeling points to a clockwise metamorphic PT path, with peak conditions of P = 18.5 kbar, T=710 degrees C, and a "warm" subduction is inferred thus. LA-ICP-MS zircon U-Pb dating yields diverse metamorphic episodes from the Neoarchean to the Palaeoproterozoic. While metamorphic zircon formed at eclogite-facies condition is identified by studying the trace element distribution and partitioning in and between zircon and co-existing eclogite-facies minerals (omphacite, garnet); consequently, Neoarchean eclogite-facies metamorphic event of ca. 2.70 Ga can be distinguished for the Gridino eclogite complex, and a regional-scale thermal event may have occurred in the period of 2.70-2.61 Ga. (C) 2015 Elsevier B.V. All rights reserved. National Natural Science Foundation of China [41202032, 412111062, 41311120071]; Geological Institute of the Russian Academy of Sciences (Moscow) SCI(E) ARTICLE xiaoli.li@pku.edu.cn 74-96 268